IMPLEMENTATION OF MOTOR WASH WASTE TREATMENT EQUIPMENT (APEL CITOR) USING THE SIMPLE FILTRATION METHOD AS AN ALTERNATIVE TO MOTOR WASHING WASTE TREATMENT - Zubaidah, Tien; Hamzani, Sulaiman; Juanda, Juanda (LPPM Univ. Ibn Khaldun Bogor, 2023)
Wastewater treatment for small-scale motorcycle washing businesses must be efficient, not require large areas of land, be easy to operate and be economical. Through this study, it is hoped that the community can apply it to the motorcycle washing business through wastewater treatment using a simple filtration method. The method chosen for this community service activity is the provision of material/counseling, discussion, and continued training in making motorbike washing waste processing equipment (APel CiTor). This activity is specifically aimed at car wash entrepreneurs whose waste has not been treated. The decrease in detergent levels is also caused by the filter media used, namely sand and banana stems. Sand whose nature is in the form of porous, degraded, and uniformity-free grains. With materials that are relatively easy to find, the community (motorcycle wash entrepreneurs) are already able to make ApeL CiTor (motorcycle washing waste processing equipment) at their respective business locations.